PENGARUH CAR, NIM, LDR, BOPO, SIZE DAN DPK TERHADAP ROA (Studi Kasus Pada Bank Umum Konvensional Yang Terdaftar Di BEI Periode 2011-2015) - Ratnaningtyas Eka Permanasari, 12.05.62.0005; Kartika, Andi (Students Journal of Accounting and Banking, 2017)
This research aims to analize ratio CAR, NIM, LDR, BOPO, Size dan DPK to ROA the conventional commercial bank in Indonesia 2011-2015. The sampling method that used in this research is purposive sampling. The technique colletion data used is the method observasi non partisipant. The F test result shows CAR, NIM, LDR, BOPO, Size dan DPK significantly influence the ROA. From the results obtained by simultaneous t test, CAR, NIM, dan DPK positive significantly influence the ROA, BOPO negative significantly influence the ROA meanwhile LDR and Size not significantly influence the profitability.Keywords: ROA, CAR, NIM, LDR, BOPO, Size dan DPK